The Womb: Beyond a Waiting Room – Nurturing the Future Generation - Hermanto Tri Joewono (Asian Journal of Health Research, 2024)
In the intricate journey of human development, the womb emerges not merely as a waiting room, but as one of the best places to lay the foundation for the growth of the human brain and human. Pregnancy, far from being solely a period of preparing for childbirth, unfolds as a golden opportunity to shape the next generation in profound ways.